Dlaczego się tłumaczy ponownie: nowe ukraińskie odczytania polskiej prozy - Saweneć, Andrij (Przekłady Literatur Słowiańskich, 2018)
Why to Retranslate: New Ukrainian Renderings of Polish Prose The paper focuses on the issue of retranslation perceived as a significant aspect of contemporary practice of literary translation into Ukrainian, exemplified by the cases of the retranslation of short stories by Bruno Schulz and Tadeusz Konwicki’s Minor Apocalypse. The emergence of new translations within a short time encourages questions about the ambitions that drove translators and publishers to present new translations of the previously translated literary works, as well as about the strategies used by translators. KEY WORDS: retranslation, Bruno Schulz, Tadeusz Konwicki, critical reception of translation, Ukrainian literary culture